Challenges of Economic Empowerment on Pesantren (Especially Privately Owned Pesantren) - Rahmah, Mutiara; Dharma, Budi; Syarbaini, Ahmad Muhaisin B. (Universitas Islam Negeri Sumatera Utara, 2024)
Apart from being a place of study, pesantrens are centers of economic development because the intensity of interaction in Islamic boarding schools is greater than in general schools. However, it turns out that several pesantrens still need help to carry out economic development and have even stopped operating. One type of Islamic boarding school that is vulnerable is one owned by individuals. The research used a qualitative approach from a community service program. The research began with systematic literature review, further analysed using a qualitative approach at one of Medan's privately owned pesantrens. Data was collected using the 'Amid mechanism with interviews, which were then analysed using reduction techniques. Pesantrens need to pay attention to financial stability, regulatory compliance, and the preservation of Islamic values in education. Finding, that one of the causes is the low financial literacy of owners, so owners tend to separate the asset entity from the management. It is a challenge to improve the economy in pesantrens. On the other hand, pesantrens are required to be able to produce economic results either by producing products and services or collaborating with residents to improve the pesantren's economy